Creazione e ricreazione di un personaggio postmoderno: il caso di Salvatore nel Nome della rosa di Umberto Eco - Grošelj, Robert (Studia Romanica Posnaniensia, 2024)
The article is dedicated to the analysis of the linguistic-textual representation of Salvatore in Umberto Eco’s novel The Name of the Rose and its Slovene, Croatian, Czech and Polish translations. The first part of the article deals with different linguistic and intertextual layers composing Salvatore’s original utterances, while the second part is devoted to Salvatore’s translated language, concentrating – primarily – on his heteroglossia and intertextuality. Salvatore is a grotesque plurilinguistic and intertextual character born out of the rich erudite immagination of Umberto Eco. The four translated Salvatores appear also as strange babelic monks whose multilingualism expands by adding a dominant Slavic linguistic element to the source-text heteroglossia. The intertextual dimension of translated Salvatores, on one hand, diminishes as most source-text citations blend into the translated linguistic mosaic, but, on the other hand, it also increases by gaining an additional metatextual (translational) dimension and, equally important, by incorporating a substantial part of Eco’s original text.